Kecenderungan penggunaan perisian Matematik di sekolah-sekolah menengah di negeri Perlis - Chan, Lay Kim (2008)
This study aims to determine the usage of teaching courseware in teaching and learning of Mathematics in secondary schools. A total of 195 teacher data samples were taken from all the 24 goverment funded schools of Perlis. All data were analyzed using the SPSS 12.0 program. The major findings of the study were that the inclination to use the teaching courseware depends on the years of experience in teaching, proficiency in computer technology, proficiency in the English language and teachers' perceptions in using the teaching courseware in the teaching and learning of Mathematics. The findings of the study shows that Mathematics teaching courseware is an effective tool during this transition period whereby the change of language in teaching and learning Mathematics is in existence. The positive inclination of the teachers to use the teaching courseware has helped to offset the present unsatisfactory conditions existing in the school in which only 69.8% of the teachers used the courseware once or twice a week. The findings also shows that there is much room for improvement to promote the usage of Mathematics teaching courseware in school. This project paper provides some suggestions to increase the usage of teaching courseware in the process of teaching and learning mathematics in secondary schools. The suggestions including the supply of one special room equipped with computer and LCD projector for each form, giving deeper and specific exposure on how to use the teaching courseware in the process of teaching and learning mathematics and conducting a short course on how to teach mathematics using the English Language. This project paper should be able to provide us with insights into different aspects related to the usage of the teaching courseware. Hence, provide information for further planning and implementation of the teaching courseware usage in the future